A genome-wide association study of early gamma-band response in a schizophrenia case–control sample. (17th November 2018) - Konte, Bettina; Leicht, Gregor; Giegling, Ina; Pogarell, Oliver; Karch, Susanne; Hartmann, Annette M.; Friedl, Marion; Hegerl, Ulrich; Rujescu, Dan; Mulert, Christoph
Abstract: Objectives: Disturbances in the gamma-frequency band of electroencephalography (EEG) measures are among the most consistently observed intermediate phenotypes in schizophrenia. We assessed whether genetic variations are associated with gamma-band activity. Methods: We performed a genome-wide association analysis of the early auditory evoked gamma-band response in schizophrenia affected subjects and healthy control individuals (in total N  = 315). Results: No marker surpassed the threshold for genome-wide significant association. Several of the markers that were closest to significance mapped to genes involved in neuronal development and the Neuregulin-ErbB signalling network, such as NRG2 and KALRN . Using a gene-set enrichment analysis, we found suggestive evidence for association with genes involved in EEG abnormality ( P  = .048). Conclusions: We identified no marker genome-wide significantly associating with gamma response; independent replication of the gene-set analysis result and larger sample sizes will be required to provide leads to cellular pathways involved in gamma-band activity.